Barringtogenol C-type Triterpenoid Saponins from the Stem Bark of Norway Maple (Acer Platanoides) - Xu, Wen; Zhang, Lu; Omar, Raed; Liu, Wei; Wei, Zhengxi; Zhang, Zengguang; Mu, Yu; Seeram, Navindra P.; Huang, Xueshi; Ma, Hang; Li, Liya (Planta Medica, 2020)
Four new barringtogenol C-type triterpenoid saponins, namely acerplatanosides A – D (1–4), along with 22 known compounds (5–26), were isolated from the stem bark of Norway maple (Acer platanoides). Their structures were elucidated on the basis of comprehensive spectroscopic analyses and chemical hydrolysis. This is the first report of triterpenoid saponins isolated from Norway maple. Compounds 1, 3, and 4 showed cytotoxicity against 4 human cancer cell lines with IC50 values ranging from 9.4 to 39.5 µM.
Keywords: Acer platanoides; Sapindaceae; Norway maple; Barringtogenol C-type; triterpenoid saponins; cytotoxicity